2016
DOI: 10.3389/fnins.2016.00013
|View full text |Cite
|
Sign up to set email alerts
|

Fischer 344 and Lewis Rat Strains as a Model of Genetic Vulnerability to Drug Addiction

Abstract: Today it is well acknowledged that both nature and nurture play important roles in the genesis of psychopathologies, including drug addiction. Increasing evidence suggests that genetic factors contribute for at least 40–60% of the variation in liability to drug dependence. Human genetic studies suggest that multiple genes of small effect, rather than single genes, contribute to the genesis of behavioral psychopathologies. Therefore, the use of inbred rat strains might provide a valuable tool to identify differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 271 publications
(382 reference statements)
4
28
0
Order By: Relevance
“…Thus, electron microscopy with serial section reconstruction is the gold standard method for studying the normal synaptic organization and its possible alterations. Here, we used Focused Ion Beam/Scanning Electron Microscopy (FIB/SEM) technology to perform a three-dimensional (3D) analysis of the synaptic organization in the neuropil in the stratum radiatum of the CA1 region of Lewis rats -an inbred rat strain that is prone to the reinforcing effects of drugs of abuse 26 . This hippocampal layer receives most afferents from the Schaffer collaterals of the CA3 pyramidal neurons -a synaptic connection that has a key role in the learning-induced synaptic potentiation of the hippocampus 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, electron microscopy with serial section reconstruction is the gold standard method for studying the normal synaptic organization and its possible alterations. Here, we used Focused Ion Beam/Scanning Electron Microscopy (FIB/SEM) technology to perform a three-dimensional (3D) analysis of the synaptic organization in the neuropil in the stratum radiatum of the CA1 region of Lewis rats -an inbred rat strain that is prone to the reinforcing effects of drugs of abuse 26 . This hippocampal layer receives most afferents from the Schaffer collaterals of the CA3 pyramidal neurons -a synaptic connection that has a key role in the learning-induced synaptic potentiation of the hippocampus 27 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study indicated that basal extracellular glutamate levels within the PFC and NAC were lower in Lewis than Fischer 344 rats (Selim and Bradberry, ). EtOH has been shown to be more reinforcing in Lewis than Fischer 344 rats, and Lewis rats self‐administer more EtOH than Fischer 344 rats (Cadoni, ). These findings, along with the current results, suggest that extracellular glutamate levels may be associated with alcohol self‐administration and drinking.…”
Section: Discussionmentioning
confidence: 99%
“…These neuroadaptations are hypothesized to underlie the development and maintenance of drug dependence and to contribute to relapse to drug seeking (Koob & Le Moal, ; Nestler, ). However, the behavioral, structural and neurochemical effects of drugs appear not only to be determined by the pharmacological properties of the drug itself, but to be also influenced by nonpharmacological factors, such as genetic susceptibility and environmental factors, (Cadoni, ; Giorgi, Piras, Lecca, & Corda, ), which play a pivotal role in modulating neuroadaptive responses to chronic drug use. Supporting this idea, many studies in different rodent strains have reported the existence of between‐strain differences in the sensitivity and in the response to drugs such as cocaine (Orsini, Bonito‐Oliva, Conversi, & Cabib, ), ethanol (Rose, Calipari, Mathews, & Jones, ), opiates (Kirkpatrick & Bryant, ), and nicotine (Freund & Wehner, ).…”
Section: Introductionmentioning
confidence: 99%